Experimental Study of Blast-Induced Vibration Characteristics Based on the Delay-Time Errors of Detonator. (8th August 2020) - Wang, Ping; Ma, Yuanjun; Zhu, Yongjian; Zhu, Jun
Abstract : The delay-time of detonators in hole-by-hole blasting is generally calculated accurately considering they have great influence on the blasting effect, such as blasting vibration and blasting slungshot. The high-precision nonel detonator and digital electronic detonator are been commonly used because of their accuracy of delay-time. However, each detonator has an allowable error range of delay-time due to the difference in manufacturing process. In the initiation network, the errors of delay-time often accumulate gradually as the number of detonators increases. Therefore, theoretical delay-time and actual delay-time with error in the detonating network were discussed based on the delay-time errors of detonators. The single-factor variable method was used to carry out the comparative test in deep hole blasting. The results showed that the particle peak vibration velocity (PPV) was 13.1783 cm/s and 3.4856 cm/s with a drop of 73.55% in comparison with a nonel detonator and digital electronic detonator, which proved that hole-by-hole blasting in the high-precision nonel detonator network was not achieved due to the delay error of detonators. Furthermore, the location distribution map of holes where the same section of detonators might occur was obtained. Finally, the probability of blasting in the same section changes with the number of blast holes was discovered by theoretical analysis, which provided a basis for accurate hole-by-hole blasting.